Places Lived: An Ego-Histoiriste and Jurisographer Discuss Living with Law in Sydney - John Docker; Ann Genovese (Law Text Culture, 2016)
The following essays, by John Docker and myself, were delivered on the final panel of the ‘Lives Lived with Law’ symposium, held at the Melbourne Law School in December 2014. The panel was called ‘Places Lived’, and our purpose was to reflect together on how intellectual traditions are inherited and inhabited in a place. The essays were written and presented as they are published here, commencing with this short introduction. We wanted to stage in public a long-standing personal discussion about what it might mean to write about Australia, in many forms and styles of address and how this involves, for us, self-fashioning a life through writing in Australia, and as Australians. In both instances, as will become evident in my essay, I have a debt to pay to John.